HUBUNGAN SENAM PROLANIS TERHADAP PENURUNAN KADAR GULA DARAH SEWAKTU PADA PASIEN DIABETES MELLITUS TIPE 2 DI PUSKESMAS SEI LEKOP - Indriasari; Elvita Nora Susana; Muthiah Ramadhani (Universitas Batam, 2024)
Background : Type 2 diabetes mellitus is a chronic metabolic disease characterized by elevated blood glucose levels in the body due to insulin resistance or inadequate insulin production. The purpose of this study is to investigatethe relationship between physical activity and blood sugar levels in patients with type 2 Diabetes Mellitus who participated in the PROLANIS program at the Sei Lekop Community Health Center in 2023. Methods : This study is an observational research with an analytical cohort design. Data collection was obtained from the medical records of patients with type 2 diabetes mellitus who are registered under BPJS. The data analysis methods include univariate analysis and bivariate analysis, with a standard error of estimate set at 5% or 0.05 Results : The results of the Wilcoxon test showed that PROLANIS exercise had a relationship with reducing blood sugar levels during type 2 diabetes mellitus patients at the Sei Lekop Community Health Center in 2023. The results of the Wilcoxon test were p = 0.001. Conclusion : Based on the results of this study, it can be concluded that there is a relationship between PROLANIS exercise and random blood sugar levels in patients with type 2 diabetes mellitus at Sei Lekop Health Center in 2023 Keywords : Diabetes Mellitus, Blood Glucose Levels, and PROLANIS Exercise.